SPATIAL ANALYSIS OF ENVIRONMENTAL SENSITIVITY FOR MITIGATION OF OIL SPILL DISASTERS IN THE SERIBU ISLANDS NATIONAL PARK - Rokhmad Khabibi; Rosadi Rosadi; Sata Yoshida Srie Rahayu (Journal of Science Innovare, 2022)
The Seribu Islands National Park (Taman Nasional Kepulauan Seribu - TNKpS) which has a marine ecosystem area that has the potential to be affected by oil spills originating from oil discharges from ships passing through the Sunda Strait and ship accidents in and out of Tanjung Priuk Port. In addition, in the TNKpS area there are also oil and gas mining companies as well as oil distribution through pipelines which have the potential to cause oil pollution due to leakage of oil distribution pipelines. The availability of maps of Environmental Sensitivity Index and comprehensive environmental data is important for the government to understand the condition of sensitive areas around oil and gas mining areas to mitigate environmental pollution due to oil spills, and can then take priority actions. to protect areas deemed sensitive. The compilation of thematic maps related to environmental sensitivity to oil spills in TNKpS shows that the beach type is not sensitive to oil spills, where the dominant beach type is gently sloping sand which is a substrate that is easy to clean when an oil spill occurs. While the component of biodiversity has the highest sensitivity. The most sensitive socioeconomic components affected by the oil spill are fish farming and marine tourism (snorkeling and diving), both of which are the main livelihoods for the people in TNKpS, especially from the tourism sector. Mitigation of oil spills in TNKpS should focus on dealing with oil spills before reaching sensitive areas where oil collection with skimmers and spraying of dispersants can be carried out before entering the coral reef area. The next step is the protection of sensitive areas from oil spills where this protection can be done by dispelling using an oil boom and directing the oil spill to a less sensitive area. The final step is cleaning the beach area in accordance with oil spill emergency response procedures. Spill simulations carried out with a duration of 3 hours, 5 hours and 24 hours showed that the oil spill had not yet reached the sensitive area when it was 3 hours, so that the ideal anticipatory oil response is to have an oil control exercise with a duration of 3 hours to protect sensitive areas.